Peptide and Oligosaccharide Nutraceutical Feeding in the Upper Rumen Stomach and Lower GI Tract in Livestock: A Commentary - Flores, D. A. (Discoveries in Agriculture and Food Sciences, 2024)
Nutraceuticals can affect transactions immunologically for health and endocrinologically for production and reproduction, specifically, referring to bioactive peptidomemics and saccharomemics in disease resistance and immunlogical balance. The nutraceuticals: Vit D2/D3, fructans and WSCs, PUFAs, alpha-lactoferrin and polysaccharides can affect SCI and as indicated by blood biomarkers. The functional amino acids (FAAs): histidine (HIS), arginine (ARG), lysine (LYS) and leucine (LEU) can affect lean body mass (LBM) accretion and milk production with bovine growth hormone (bGH)/bovine growth-releasing hormone (bGRH) and prolactin. The two prebiotic nutraceuticals referred to can be applied to “designer” oligomers from enriched seed proteins and polysaccharides to improve feed nutritive value (NV). High non-fibrous carbohydrate (NFC) and water-soluble carbohydrate (WSC) grasses can also provide higher-end energy forages. There are, thus, proteinogenic approaches that can be used for supplemental feeding. It is suggested that lower quality residual feedstocks can be converted to food-feed applications and can involve pretreating of fibrous carbohydrates (FC) and NFC, conversion to natural sugars and sweeteners, and “shuffling” copolymerization. Applications can be made to fishmeal for production and health. Slowed reaction enzymes (SRE) can be used with so-called osmolytic resins to study behaviour of pre-formed amino acids (PFAAs) in the rumen milieu to fit rumen protein solubility with use of inhibitors to both plant and microbial proteases, modulating as a result the MCP and “escape” protein flows to the lower GI tract. Clean tech can produce seed-derived proteins using “bulk” cell culturing (processed and unprocessed) and extracted/enriched yeast culturing. There is a need to verify the prebiotic binding receptors in the small intestines (SI) (e. g. gut-associated lymphoid tissues, GALT, and as speculated the SI’s jejunum).